التدقيق الاتصالي و دوره في تشخيص الأزمات في مجال الأمن المروري ، الجزائر نموذجا - بودهان, يامين (جامعة الوادي - University of Eloued, 2021)
ستستعرض المداخلة التالية أهم خطوات التدقيق الاتصالي في مجال الأمن المروري في الجزائر تحديدا، و سنتطرق لأهم الأسئلة الاستراتيجية التي تطرح حتى نفهم الوضعيات الاتصالية بشكل جيد قبل الشروع في تنفيذ أية حملة إعلامية مرورية ، إذ غالبا ما يتم تجاهل التدقيق الاتصالي في إدارة الاتصال المروري ، لذا كثيرا ما تفشل حملات التوعية الأمنية في تغيير اتجاهات وسلوكيات المواطنين إيجابا، وستحاول المداخلة التالية تقديم نموذج نظري لإعداد خطة تدقيقية تكون مناسبة للتنفيذ على مستوى إدارة التدقيق الاتصالي الأمني المروري. The following intervention will review the most important audit communication steps in the field of security congestion in Algeria in particular, and we will look for the most important strategic questions that arise even understand communication well before embarking on any media campaign traffic, as it is often ignored audit communication in the management of communication traffic, so often security awareness campaigns fail to change attitudes and behaviors of citizens positively, and the following intervention will try to provide a theoretical model to prepare a plan auditing be suitable for implementation at the level of communication security management audit congestion.
The communication and its role in the diagnosis of crises In the field of road safety, Algeria is a model
مقال
Keywords: التدقيق ، الاتصال ، تشخيص ، الأزمات ، الأمن; communication , crisis , security